2019
DOI: 10.1007/s00109-019-01859-w
|View full text |Cite
|
Sign up to set email alerts
|

The integrated stress response promotes B7H6 expression

Abstract: The B7 family member, B7H6, is a ligand for the natural killer cell receptor NKp30. B7H6 is hardly expressed on normal tissues, but undergoes upregulation on different types of tumors, implicating it as an attractive target for cancer immunotherapy. The molecular mechanisms that control B7H6 expression are poorly understood. We report that in contrast to other NK cell ligands, endoplasmic reticulum (ER) stress upregulates B7H6 mRNA levels and surface expression. B7H6 induction by ER stress requires protein kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…It was reported that ISR promotes the expression of potential target for immunotherapy (Obiedat et al, 2020). Thus, ISR may play a role in cancer immunotherapy.…”
Section: Dual Roles Of the Integrated Stress Response In Cancermentioning
confidence: 98%
See 1 more Smart Citation
“…It was reported that ISR promotes the expression of potential target for immunotherapy (Obiedat et al, 2020). Thus, ISR may play a role in cancer immunotherapy.…”
Section: Dual Roles Of the Integrated Stress Response In Cancermentioning
confidence: 98%
“…BTdCPU and ONC201 activates HRI (Kline et al, 2016;Chen et al, 2011). Bortezomib, gemcitabine, lopinavir and CCT020312 selectively activates PERK (Narita et al, 2015;Palam et al, 2015;Obeng et al, 2006;Obiedat et al, 2020;Stockwell et al, 2012). BEPP works on PKR activation (Figure 3) (Hu et al, 2009).…”
Section: Enhanced Integrated Stress Response Signaling Viamentioning
confidence: 99%
“…These different observations of how nel navir inhibits herpesvirus production could be related to the differences in how the two viruses replicate and the optimal cell culture system that each virus is grown in. We believe, for KSHV it is the effect of the drug on the ISR [24,34] which then manifests as a block in virus capsid assembly. This was evident in the viral protein analysis which showed that the accumulation of some KSHV proteins was inhibited by nel navir.…”
Section: Discussionmentioning
confidence: 97%
“…[1][2][3] However, during malignant transformation B7-H6 expression increases due to the activation of endoplasmic reticulum stress, oncogenes such as MYC, or epigenetic mechanisms. [4][5][6][7] B7-H6 was first identified as a ligand of NKp30/NCR3, an activating receptor of NK cells that triggers cytotoxicity and cytokine secretion acting against tumor cells. 8 However, in recent years it has been shown that B7-H6 has a non-immunological role in tumorigenesis because it can inhibit apoptosis and promote the proliferation of tumor cells.…”
Section: Introductionmentioning
confidence: 99%